Plasmonic–magnetic dual-functional graded nanoparticles with oxide shell passivation designed for bioapplications. (4th September 2018) - Kitaura, Ryoichi; Takahashi, Mari; Mohan, Priyank; Higashimine, Koichi; Mott, Derrick; Maenosono, Shinya
Abstract: Plasmonic–magnetic dual-functional nanoparticles consisting of a graded structure with plasmonic silver (Ag) and ferromagnetic iron–cobalt–platinum alloy (FeCoPt) components mixed at the atomic level with a composition gradient were chemically synthesized. The surfaces of the nanoparticles were uniformly covered with iron oxide (Fe x O y ). The resulting nanoparticles possessed a graded-core/oxide-shell structure and unique physical properties. In addition, the surfaces of the nanoparticles were biotinylated to enhance their versatility for use in various bioapplications such as bioimaging, biosensing, immunodiagnosis, and hyperthermia.